Projeto automático de controlador de velocidade sem sensor mecânico para motores de indução trifásicos - Einloft, Diego (2008)
This works proposes parameters estimation algorithm to auto-tune the control laws of a speed sensorless servo. The identification process of the electrical and mechanical parameters is based on recursive least squares method (RLS) and utilizes just measured stator currents. The electrical parameters are obtained by the transfer function of the motor with locked rotor. Hence, this eliminates the need to realize classical tests for the electrical parameters obtention and impose robustness to the controller for parameters variations caused by aging of materials. Thus, the electrical parameters are used to project the current controllers and the rotor speed is estimated by a model reference adaptive systems (MRAS). The structure of MRAS is composed by two systems (reference model and adaptive system) based on instantaneous reactive power and using an adaptation mechanism. On the other hand, to obtain a robust control when the system is subject to disturbances or load s variations, mechanical parameters are identified using estimated rotor speed and mechanical model of the induction motor (IM). Finally, for the speed control is used a proportional plus integral controller (PI) self-tuned through the estimated inertia.